Knee flexion with quadriceps cocontraction: A new therapeutic exercise for the early stage of ACL rehabilitation - Biscarini, A.; Contemori, S.; Busti, D.; Botti, F. M.; Pettorossi, V. E. (Journal of Biomechanics, 2016)
Quadriceps strengthening exercises designed for the early phase of anterior cruciate ligament (ACL) rehabilitation should limit the anterior tibial translation developed by quadriceps contraction near full knee extension, in order to avoid excessive strain on the healing tissue. We hypothesize that knee-flexion exercises with simultaneous voluntary contraction of quadriceps (voluntary quadriceps cocontraction) can yield considerable levels of quadriceps activation while preventing the tibia from translating forward relative to the femur. Electromyographic activity in quadriceps and hamstring muscles was measured in 20 healthy males during isometric knee-flexion exercises executed near full knee extension with maximal voluntary effort of quadriceps cocontraction and external resistance (R) ranging from 0% to 60% of the 1-repetition maximum (1RM). Biomechanical modeling was applied to derive the shear (anterior/posterior) tibiofemoral force developed in each exercise condition. Isometric knee-flexion exercises with small external resistance (R=10% 1RM) and maximal voluntary effort of quadriceps cocontraction yielded a net posterior (ACL-unloading) tibial pull (P=0.005) and levels of activation of 32%, 50%, and 45% of maximum voluntary isometric contraction, for the rectus femoris, vastus medialis, and vastus lateralis, respectively. This exercise might potentially rank as one of the most appropriate quadriceps strengthening interventions in the early phase of ACL rehabilitation.